Manajemen Keuangan Penerimaan Peserta Didik Barudi Pondok Pesantren Al-Ma’mur - Rosiana, Indah; Nursekha, Aulia (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This article aims to describe and analyze financial management in the New Student Admission (PPDB) process at Pondok Pesantren Al-Ma'mur, covering budget planning, fundraising, fund utilization, as well as reporting and accountability systems. This study employs a qualitative-descriptive approach, with data collected through in-depth interviews, participatory observation, and analysis of PPDB financial documents. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that financial management of PPDB at Pondok Pesantren Al-Ma'mur has been implemented systematically through four main stages: planning, organizing, implementation, and evaluation. The budget planning system is based on applicant projections; organizational management involves a clearly defined committee structure; fund receipt mechanisms utilize a coded receipt system; and financial reporting is conducted periodically (daily, weekly, and final reports). Effective PPDB financial management plays a crucial role in maintaining transparency, accountability, and operational stability of the pesantren, while also enhancing public trust. However, the digitalization of payment systems and the improvement of human resource capacity remain challenges that need to be addressed to further enhance the effectiveness of PPDB financial management.